Peningkatan Literasi Sains Mahasiswa Pendidikan Fisika Melalui Pembuatan LKPD Berbasis Sosio Saintifik - Effendi Effendi; Arini Rosa Sinensis; Thoha Firdaus (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2023)
This research is a type of research that focuses on efforts to increase student scientific literacy. The purpose of this study is to characterize the profile of increasing students' scientific literacy abilities through the development of socio-scientific-based worksheets. The research sample was 2C semester students in the Physics Education Study Program for the 2022–2023 academic year, with a total of 10 students, and the research design used a one-group pretest-posttest design. The findings show that the average N-gain obtained is 0.48, which is included in the moderate improvement category. The significance level of 0.00, less than 0.05 (sign. 0.05), was found in the results of hypothesis testing using the t test, indicating that Ho was not accepted. Based on the test results, there is a significant difference between the level of scientific literacy of students before and after implementing learning by making socioscience-based worksheets. This study shows how teaching using socio-scientific-oriented worksheets can raise the profile of students' scientific literacy abilities.